Visible‐Light‐Enabled Synthesis of Pyridyl Benzamides via Oxidative Decarbethoxylation using Copper(I) Iodide/Air at Room Temperature. Issue 6 (24th April 2019) - Sharma, Anup Kumar; Kumar, Promod; Vishwakarma, Ramesh Kumar; Singh, Krishna Nand
Abstract: An efficient synthesis of N ‐(pyridin‐2‐yl)benzamides has been developed by the reaction of 2‐aminopyridines and ethyl arylacetates via oxidative decarbethoxylation using visible light/CuI/O2 in acetonitrile at room temperature. Abstract : Copper lamp : A facile visible‐light‐induced aerobic oxidative amidation using 2‐aminopyridines and ethyl arylacetates is described via C−C bond cleavage/C−N bond formation at room temperature. This reaction involves a benzylic methylene oxidation, imine formation, and oxidative decarbethoxylation under environmentally benign conditions.